Perbedaan Hasil Belajar Mahasiswa Teknik Elektro dalam Mata Kuliah Mesin-Mesin Listrik Ditinjau dari Jalur Masuk dan Latar Belakang Pendidikan - Nabila, Ammilia Dara; Usmeldi, Usmeldi (Jurnal Pendidikan Teknik Elektro, 2025)
Learning outcomes are an indicator of the mastery of lecture material that students have achieved. Learning outcomes can be used as a benchmark for student success in lectures. This research aims to describe differences in learning outcomes in the Electrical Machines Course for Electrical Engineering students entering 2020. The type of research that the author conducted was descriptive comparative research. Data collection was carried out using documentation instruments obtained from the Technical Implementation Unit for Data and Technology Services, Padang State University in the form of learning outcomes for the Electrical Machines Course, entry selection routes, and educational background of Electrical Engineering Education students entering 2020. It can be concluded that there is no significant difference in learning outcomes for the Electrical Machines course in terms of the SNMPTN, SBMPTN and Independent Selection entry groups. Where the highest average is students from the Independent Selection route and the lowest average is students from the SNMPTN route. Based on educational background, there are also no significant differences between SMK, SMA, and MA. Where the highest average score is for students with an MA education background and the lowest average is for students with a vocational school education background.